2020
DOI: 10.6004/jnccn.2020.0016
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer, Version 3.2020, NCCN Clinical Practice Guidelines in Oncology

Abstract: Several new systemic therapy options have become available for patients with metastatic breast cancer, which have led to improvements in survival. In addition to patient and clinical factors, the treatment selection primarily depends on the tumor biology (hormone-receptor status and HER2-status). The NCCN Guidelines specific to the workup and treatment of patients with recurrent/stage IV breast cancer are discussed in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
660
0
30

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,038 publications
(694 citation statements)
references
References 180 publications
(250 reference statements)
4
660
0
30
Order By: Relevance
“…Cancer November 15, 2019 effects, 33,34 but studies of these treatments have not yet reported improvements in adherence. Differences between physicians and patients in perceptions of medicines may also pose important barriers to adherence: patients in 1 large AET study reported that an important barrier to continuing AET was "I was not sure if it (the medication) was helping," 35 and a meta-analysis of 5 randomized studies showed that educational interventions to address such issues had little impact on adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer November 15, 2019 effects, 33,34 but studies of these treatments have not yet reported improvements in adherence. Differences between physicians and patients in perceptions of medicines may also pose important barriers to adherence: patients in 1 large AET study reported that an important barrier to continuing AET was "I was not sure if it (the medication) was helping," 35 and a meta-analysis of 5 randomized studies showed that educational interventions to address such issues had little impact on adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The resource‐stratified guidelines for breast cancer treatment describe the laboratory testing components needed to treat breast cancer 18,19 . For maximally resourced settings, this includes the traditional prognostic factors and the biomarkers and molecular tests mentioned above 20 . For the basic level of essential pathology, the list includes the traditional prognostic factors and ER/PR testing, but it excludes HER2 testing because the cost of therapy is very high.…”
Section: Resource‐stratified Guidelines For Breast Pathology Evaluationmentioning
confidence: 99%
“…Currently, neoadjuvant therapy for luminal A patients includes NAC and neoadjuvant endocrine therapy. NAC is still the preferred treatment [6,7]. The chemotherapy regimens of this type of patients are based on anthracycline and taxane, but the effective rate is only 13-14.1% [8,9],sometimes even lower than the effective rate of neoadjuvant endocrine therapy [10], and the adverse events of chemotherapy will cause unnecessary pain for patients who will not bene t from it.…”
Section: Introductionmentioning
confidence: 99%